PENGENDALIAN PIUTANG SEBAGAI USAHA UNTUK MENINGKATKAN EARNING POWER STUDI KASUS PT SEMEN GRESIK (PERSERO) TBK - Bahari, Chabib (Fakultas Ekonomi Universitas Gresik, 2016)
Cementbusiness grows more global. Competition becomes tighter which are not only relying on the supply guarantee, product quality even more promotion.Sales Price aspect of product and flexibility on payment terms has begun the otherinterested aspect for consumers.Distributors as an intermediary party are also expecting the same, therefore, Semen Gresik as a producer of cement has applied sales by credit withbonds. Sales by credit has proven increasing sales volume ofcement but alsobrought another impact for increasing receivable amount. It emerged when increase of sales volume occurred and or there ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¹Ã…â€œs price increase; generally increase of sales volume occurred in 2nd semester annually, whereas priceincrease could be occurred in 1st semester and 2nd semester.Within the period of year -1998 ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â 2002 there were transitions on the application system, from FOXBASE to SYBASE (year 2000) and SYBASE to JD. Edward (yeÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¥r 2002) that caused Feceivable amount as recorded by Semen Gresik was different with the amount as recorded by the distributor. When adistributor paid their debt; it will not automatically reduce the receivable amount but it will be recorded in a temporary account as deposit money that will be reconciled by the both parties. It will influence at least time for drawing thereceivable amount; more reconciliation, longer payment will be done by distributor.Refer to an audit conducted in Semen Gresik based Ill Distributors spread in all market areas, in 5 year period since 1998 to 2002 shown that Semen Gresik has borne huge receivable amount, with the cycle of it can be categorized slow compared internationally with other world class enterprises and surely brought risk for unpaid that finally will impact to the company loss.